Proceedings of the Sixth World Congress of Jewish Studies (1977)
includes G. Cardascia, Droits cunéiformes et droit biblique; M. Cogan, The Ahaz Altar: On the Problem of Assyrian Cults in Judah; S. Kaufman, Prediction, Prophecy and Apocalypse in the Light of New Akkadian Texts; E. Lipiński, An Assyrian-Israelite Alliance in 842/841 B.C.E.?; M. Weinfeld, Judge and Officer in Ancient Israel and in the Ancient Near East.